Surgical Treatment in Childhood-onset Inflammatory Bowel Disease–A Nationwide Register-based Study of 4695 Incident Patients in Sweden 2002-2014. (27th September 2017) - Nordenvall, Caroline; Rosvall, Oda; Bottai, Matteo; Everhov, Åsa H; Malmborg, Petter; Smedby, Karin E; Ekbom, Anders; Askling, Johan; Ludvigsson, Jonas F; Myrelid, Pär; Olén, Ola
Abstract: Background and Aims: The incidence of childhood-onset [< 18 years] inflammatory bowel disease [IBD] is increasing worldwide, and some studies suggest that it represents a more severe disease phenotype. Few nationwide, population-based studies have evaluated the surgical burden in patients with childhood-onset IBD, and whether the improved medical treatment has influenced the need for gastrointestinal surgery. The aim was to examine whether the surgical treatment at any age of patients with childhood-onset IBD has changed over time. Methods: In a nationwide cohort study we identified 4695 children [< 18 years] diagnosed with incident IBD in 2002–2014 through the Swedish Patient Register [ulcerative colitis: n = 2295; Crohn's disease: n = 2174; inflammatory bowel disease-unclassified: n = 226]. Abdominal [intestinal resections and colectomies] and perianal surgeries were identified through the Swedish Patient Register. The cumulative incidences of surgeries were calculated using the Kaplan-Meier method. Results: In the cohort, 44% were females and 56% males. The median age at inflammatory bowel disease diagnosis was 15 years and the maximum age at end of follow-up was 31 years. The 3-year cumulative incidence of intestinal surgery was 5% in patients with ulcerative colitis and 7% in patients with Crohn's disease, and lower in children aged < 6 years at inflammatory bowel disease diagnosis [3%] than in those aged 15–17 years at diagnosis [7%]. Calendar period of inflammatory bowel disease diagnosis was not associated with risk of surgery. Conclusion: Over the past 13 years, the risk of surgery in childhood-onset inflammatory bowel disease has remained unchanged.